Robotic Transanal Minimally Invasive Surgery for Rectal Lesions. (April 2020) - Yao, Hong-Liang; Ngu, James Chi-Yong; Lin, Yen‑Kuang; Chen, Chia‑Che; Chang, Sheng-Wei; Kuo, Li-Jen
Background . Transanal minimally invasive surgery (TAMIS) was developed as a less aggressive alternative treatment for rectal lesions. The purpose of this study was to report the results of robotic TAMIS for such patients. Methods . Patients eligible for TAMIS were operated on using the da Vinci robotic surgical system and GelPOINT Path Transanal Access Platform. Patient demographics, lesion characteristics, perioperative data, complications, and follow-up of all patients were recorded retrospectively. Results . Between March 2015 and August 2018, 24 patients underwent robotic TAMIS by using the da Vinci Si or Xi. The median operative time was 129.6 minutes, and the estimated blood loss was minimal. The mean length of hospital stay was 4.6 days, with no operative complications and no 30-day mortality. There were no statistically significant differences in clinical results and pathological outcomes between the 2 generations of da Vinci systems. Conclusions . With the use of robotic technology, transanal local excision for rectal lesions can be performed with relative ease and safety and can be potentially decreasing the morbidity associated with more aggressive surgical techniques.